A New Look at the Impact of Maximizing on Unhappiness: Two Competing Mediating Effects - Peng, Jiaxi; Zhang, Jiaxi; Zhang, Yan; Gong, Pinjia; Han, Bing; Sun, Hao; Cao, Fei; Miao, Danmin (Frontiers in Psychology, 2018)
The current study aims to explore how the decision-making style of maximizing affects subjective well-being (SWB), which mainly focuses on the confirmation of the mediator role of regret and suppressing role of achievement motivation. A total of 402 Chinese undergraduate students participated in this study, in which they responded to the maximization, regret, and achievement motivation scales and SWB measures. Results suggested that maximizing significantly predicted SWB. Moreover, regret and achievement motivation (hope for success dimension) could completely mediate and suppress this effect. That is, two competing indirect pathways exist between maximizing and SWB. One pathway is through regret. Maximizing typically leads one to regret, which could negatively predict SWB. Alternatively, maximizing could lead to high levels of hope for success, which were positively correlated with SWB. Findings offered a complex method of thinking about the relationship between maximizing and SWB.